Epidemiology of type 1 diabetes mellitus in Basrah, Southern Iraq: A retrospective study. (November 2017) - Almahfoodh, Dhaighum; Alabbood, Majid; Alali, Ahmed; Mansour, Abbas
Highlights: This is the first epidemiological study on type 1 diabetes mellitus in Iraq. The overall mean age at first diagnosis was 15.3 ± 9 years and it was significantly higher in men. The prevalence was 87 per 100, 000 and it is lower than neighboring countries. The average annual incidence rate of type 1 diabetes was 7.4 per 100, 000 which places Iraq in the intermediate group. This study provides a baseline for assessing future changes in the epidemiology of type 1 diabetes mellitus in Iraq. Abstract: Aims: To investigate the epidemiology of type 1 diabetes mellitus (T1DM) in Basrah city, Southern Iraq, between 2012 and 2016 among people 0–40 year old. Methods: This was a retrospective data analysis of electronic archives for patients with T1DM registered in Faiha Specialized Diabetes, Endocrine, and Metabolism Center (FDEMC), which is a tertiary referring Center in Basrah. The data include electronic database from August 2008 to February 2016. Incidence and prevalence rates are expressed per 100, 000. Population of Basrah estimates were derived from official data of The Ministry of Planning of Iraq. Results: There were 2536 people registered at FDEMC. Of them 53.5% were males. The overall mean age at first diagnosis was 15.3 ± 9 years and it was significantly higher in males; p value 0.0005. The prevalence rate of T1DM in people 40 years old and younger in 2016 was 87 per 100, 000. Between 1 January 2012 and 31 December 2016, there were 818 identified new cases of T1DM. Of these, 417 (50%) were males. The average annual incidence rate of T1DM was 7.4 per 100, 000 (95% CI, 7.1–8.1). Conclusions: The incidence of T1DM in Basrah lies in the "intermediate group" according to DIAMOND project group classification. The incidence was increasing over the last three years. The data produced by this study provide a baseline for assessing future changes in the epidemiology of T1DM in Iraq.